The needs of lifelong learning from the perspectives from the working adults - Nor Syahidatun Salmi Mansor, (2008)
This study explores the needs of lifelong learning from the perspectives of working adults focusing on the employees of METEOR Group of Companies. The study addresses concerns via its three stated objectives namely to identify profiles of staff who pursue formal learning in the organization, identifying reasons for pursuing learning as well as identifying constraints in the pursuance of lifelong learning. The data for this study embraces the email messages, interview transcripts as well as communication via synchronous mediated technology, namely Yahoo Messenger. The data collected has been processed using statistical fwnction embedded in SPSS programme. Factor analysis techniques have also been used in the effort to process data. Thus far, data collected could not be further analyzed due to small numbers recorded on the staff who currently pursuing learning. Findings of the study had generated reasons for pursuing lifelong learning that is basically to increase and enhance self opportunity, for the financial and economic stability as well as for self satisfaction of oneself. The study also discovered the awareness among the non-pursuance of lifelong learning on the importance of continuous learning. The existence of the awareness among the non pursuance was definitely hindered by the constraints discovered in the study. The major constraints recorded are work commitment, financial as well as time constraint. Apparently, these constraints had strongly triggered that majority of the staff who pursue learning are at the non-executive level as compared to the executive and middle management. Indirectly it shows that the non-executive level are committed to improve their current well being and perhaps for the reason that there are less burden in their present work which allows them to pursue higher 1earning.The findings will contribute towards the organization efforts in enhancing and established skilled human capital within the organization. The findings and recommendation of the study would serve as a relevant tool in harnessing employees' development as well as sustaining the employability of respective staff. The study offers positive views for further study to be explored in order to attain a better understanding among the new employees of the organization besides providing actual assistances in L creating and provoking awareness amongst its employees towards the importance of lifelong learning. To sustain and survive in rapid changing world, organization has to be [i more proactive in generating skilled human capital for the bettennent of the organization E as well as the employees, in particular. (Author's abstract)